2021
DOI: 10.1108/ict-11-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the new forms of employment relationship: implications and insights for human resource development

Abstract: Purpose The labor market has witnessed the increase of the new forms of employment relationship (freelancers, contingent workers, and gig workers) due to the COVID-19 outbreak, generating new workforce patterns that represent a significant challenge for human resource development (HRD) professionals in organizations. Studies that have addressed these new forms of employment relationship and HRD during this pandemic are sparse. This paper aims to broaden the scope of HRD research by exploring the implications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Due to these lockdown measures, around 140 million people around the globe have lost their jobs (Chakraborty, 2020). Further, COVID-19 pandemic has highly impacted some specific segments of workforce such as women, self-employed, low wage workers, temporary workers and atypical or non-standard employees such as freelancers and gig workers (Pouliakas and Branka, 2020;Hamouche and Chabani, 2021). The impact of this pandemic has been quite asymmetric as the workforce segment has suffered the most in almost all the countries (Fana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these lockdown measures, around 140 million people around the globe have lost their jobs (Chakraborty, 2020). Further, COVID-19 pandemic has highly impacted some specific segments of workforce such as women, self-employed, low wage workers, temporary workers and atypical or non-standard employees such as freelancers and gig workers (Pouliakas and Branka, 2020;Hamouche and Chabani, 2021). The impact of this pandemic has been quite asymmetric as the workforce segment has suffered the most in almost all the countries (Fana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the employment market witnessed an increase in the flexible form of work arrangements (e.g. subcontracted work, such as temporary agency work, freelancers and gig economy) (Spurk and Straub, 2020; Hamouche and Chabani, 2021), as a consequence of the uncertainty generated by this pandemic. For instance, Gartner's report in the US revealed that “ 32% of organizations are replacing full-time employees with contingent workers as a cost-saving measure ” (Baker, 2020).…”
Section: Theoretical Foundation Literature Review and Research Questionsmentioning
confidence: 99%
“…Indeed, studies revealed that COVID-19 generated a “great resignation” sweeping worldwide workplaces (Allman, 2021; Sheather and Slattery, 2021). Many individuals were either quitting their job or looking for a career change (Allman, 2021), and this can weigh heavily on sectors already suffering from a workforce shortage, such as healthcare (Hamouche and Chabani, 2021; Sheather and Slattery, 2021; Hamouche, 2022). In the US, for example, the Bureau of Labor Statistics (2021) showed that the quitting level and rate increased to a series high of 4 million and 2.7%, in April 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing from Arora and Suri (2020), the authors set out a general framework for evaluating and recrafting HRD for the pandemic and post-pandemic world. They call this the “4-R crisis-normalcy model of HRD” (Hamouche and Chabani, 2021, p. 371). This cycles through redefining HRD, relooking at HRD, redesigning HRD and finally reincorporating HRD into the organization.…”
Section: Adapting Hrd To Covid-19mentioning
confidence: 99%